Intertwined translational regulations set uneven stoichiometry of chloroplast ATP synthase subunits - Drapier, Dominique (Nature Publishing Group, 2007)
The (C)F1 sector from H(+)-ATP synthases comprises five subunits: α, β, γ, δ and ɛ, assembled in a 3:3:1:1:1 stoichiometry. Here, we describe the molecular mechanism ensuring this unique stoichiometry, required for the functional assembly of the chloroplast enzyme. It relies on a translational feedback loop operating in two steps along the assembly pathway of CF1. In Chlamydomonas, production of the nucleus-encoded subunit γ is required for sustained translation of the chloroplast-encoded subunit β, which in turn stimulates the expression of the chloroplast-encoded subunit α. Translational downregulation of subunits β or α, when not assembled, is born by the 5′UTRs of their own mRNAs, pointing to a regulation of translation initiation. We show that subunit γ, by assembling with α(3)β(3) hexamers, releases a negative feedback exerted by α/β assembly intermediates on translation of subunit β. Moreover, translation of subunit α is transactivated by subunit β, an observation unprecedented in the biogenesis of organelle proteins.